2018
DOI: 10.3390/ijerph15081717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bioaugmentation on Biogas Yields and Kinetics in Anaerobic Digestion of Sewage Sludge

Abstract: Bioaugmentation with a mixture of microorganisms (Bacteria and Archaea) was applied to improve the anaerobic digestion of sewage sludge. The study was performed in reactors operating at a temperature of 35 °C in semi-flow mode. Three runs with different doses of bioaugmenting mixture were conducted. Bioaugmentation of sewage sludge improved fermentation and allowed satisfactory biogas/methane yields and a biodegradation efficiency of more than 46%, despite the decrease in hydraulic retention time (HRT) from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…The enzymes provided by Archaea result in higher reaction rates and reduce the contamination problems [ 44 ]. This was confirmed by the recent study of Lebiocka et al [ 45 ] on the anaerobic digestion of sewage sludge. The authors reported a significant increase in the rate constant of biogas production along with the MAB dose despite the decrease in hydraulic retention time.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…The enzymes provided by Archaea result in higher reaction rates and reduce the contamination problems [ 44 ]. This was confirmed by the recent study of Lebiocka et al [ 45 ] on the anaerobic digestion of sewage sludge. The authors reported a significant increase in the rate constant of biogas production along with the MAB dose despite the decrease in hydraulic retention time.…”
Section: Introductionsupporting
confidence: 80%
“…In the present study, the influence of bioaugmentation on total metal concentrations in digestate was examined for anaerobic digestion of sewage sludge. The presented results are the continuation of previously mentioned research [45]. The novel aspect of the work involved evaluating the effect of adding a mixture of wild the bacteria and Archaea from Yellowstone National Park, USA, on the metal contents in the digestate, and determining how it may influence the environment.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…While microbial consortia may offer a broader degrading potential, they are less biologically stable and controllable than single microbial strains that are hence more often used [9]. The role of bioaugmentation in enhancing methane production was demonstrated for various substrates, which can be grouped into four main categories: sewage sludge [10]; animal manures [11,12]; food industry waste [13,14], and energy crops or agricultural residues [15,16]. These examples are related to studies performed in lab-scale digesters.…”
Section: Introductionmentioning
confidence: 99%